2014
DOI: 10.1016/j.yexcr.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The combination of glutamate receptor antagonist MK-801 with tamoxifen and its active metabolites potentiates their antiproliferative activity in mouse melanoma K1735-M2 cells

Abstract: Recent reports suggest that N-methyl-d-aspartate receptor (NMDAR) blockade by MK-801 decreases tumor growth. Thus, we investigated whether other ionotropic glutamate receptor (iGluR) antagonists were also able to modulate the proliferation of melanoma cells. On the other hand, the antiestrogen tamoxifen (TAM) decreases the proliferation of melanoma cells, and is included in combined therapies for melanoma. As the efficacy of TAM is limited by its metabolism, we investigated the effects of the NMDAR antagonist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In our laboratory, we have demonstrated that the key active metabolite of tamoxifen, endoxifen, has a more powerful cytostatic action in a mouse melanoma cell line than the prodrug (Ribeiro et al, 2013a(Ribeiro et al, , 2014, suggesting that the efficacy of tamoxifen in melanoma may also be limited by the individual metabolism or the simultaneous administration of medication, as described in breast cancer. Thus, future trials in melanoma patients taking tamoxifen should include therapeutic drug monitoring.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our laboratory, we have demonstrated that the key active metabolite of tamoxifen, endoxifen, has a more powerful cytostatic action in a mouse melanoma cell line than the prodrug (Ribeiro et al, 2013a(Ribeiro et al, , 2014, suggesting that the efficacy of tamoxifen in melanoma may also be limited by the individual metabolism or the simultaneous administration of medication, as described in breast cancer. Thus, future trials in melanoma patients taking tamoxifen should include therapeutic drug monitoring.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, recent work performed in our laboratory has demonstrated that both endoxifen and 4-hydroxytamoxifen are more effective than the parent drug in the reduction of the mouse melanoma cell line K1735-M2 proliferation (Ribeiro et al, 2013a(Ribeiro et al, , 2014, which is a model of aggressive melanoma (Repesh, 1989). These results raise the question whether the efficacy of tamoxifen in melanoma may also be affected by individual metabolism variability and simultaneous intake of other drugs, as demonstrated in breast cancer, and should be taken into account in future studies in melanoma patients in order to establish the better patient profile for a successful response to tamoxifen.…”
Section: Diseasementioning
confidence: 99%
“…Interestingly, peripheral NMDA receptors are also drug targets to evade multidrug resistance in cancer by virtue of their ability to downregulate ABC transporters 97 . Such is case of compound MK-801, which noncompetitively antagonizes NMDA receptor 98 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mouse melanoma cell proliferation was inhibited by blocking NMDA receptors with MK-801 and the effect was amplified when antiestrogens were associated; among all iGluRs, only the blocking of NMDA receptors was effective in controlling melanoma growth [ 116 ].…”
Section: Neurotransmitters and Melanomamentioning
confidence: 99%